Best Answer

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

Q: Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9a +8 -2a -3 -5a = 2a +5

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

It is: 7(2a+3) when factorised

Related questions

3b -1

2a-3+4b-2a-b-3+5=3b-1

2a*4b*(-3c) = ? 2 * 4 * -3 * a * b * c = ? -24abc

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

4b - 1 = -4 + 4b + 3first, simplify and add together what you can.4b - 1 = -1 + 4b4b = 4bbecause 4b is always equal to 4b, the answer is infinite.

2a+5

2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4

There are no like terms here.

9a +8 -2a -3 -5a = 2a +5

(a - b + 1)(a + b - 3)

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1